Electroencephalographic changes as neuroscience-based cognitive skill training program - Sittiprapaporn, Phakkharawat (Asian Journal of Medical Sciences, 2020)
Background: Brain is an organ that is easily affected by the physical changes.Abnormalities are known to occur with the brain in terms of memory, eyesight, intellect, and balance as the brain is an organ that is easily affected by the physical changes. Executive functions have been shown to be related to academicachievement and the ability to learn, as well as a range of a neurodevelopmental disorders. The failure of many traditional educational interventions for students with specific learning disabilities may be attributed to large deficits in executive functions, including working memory and inhibition. Aims and Objective: This study examined how BrainWare SAFARI, a computer-based training, aid students with specific learning disabilities in enhancing their executive functions and specific learning disabilities. Materials and Methods: The present experimental study examined the effectiveness of a specific 12-week neuroscience-based, cognitive skills computer-training program, BrainWare SAFARI, on the cognitive processing of elementary students with specific learning disabilities. Results:The results of this study showed that all students Participants were able to complete a sufficient number of sessions in BrainWare SAFARI experienced significant improvements in multiple areas of cognitive processing. The results showed that the attention level changed with statistically significant while the meditation level was not changed. Conclusion: Thus, this neuroscience-based, cognitive skills computer-training program, BrainWare SAFARI, could result in increased academic performance.